Rehumanisasi Sains dan Teknologi: Integrasi Kearifan Buddhis dan Stem di Era Industri 5.0 dan Society 5.0: Penelitian - Budiono; Julia Surya; Aleks Effendi; Eklianti; Leon Gilberto Medellin Lopez; Yaka Paweja (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The development of science and technology, particularly Artificial Intelligence (AI), in the era of Society 5.0 presents significant opportunities while simultaneously posing serious challenges in the form of increasing tendencies toward dehumanization. This article aims to examine how Buddhist teachings derived from thematic suttas can function as an ethical framework in the process of rehumanizing science and technology. The study employs a literature review method with a qualitative–philosophical approach to relevant Buddhist texts, combined with a critical analysis of contemporary discourses on AI and technology. The findings indicate that Buddhist values such as wisdom (paññā), loving-kindness (mettā) and compassion (karuṇā), as well as an orientation toward liberation from suffering (dukkha), can serve as an “ethical firewall” in the development and application of technology. The integration of Buddhist teachings is not intended to reject technological progress, but rather to guide it so that it remains aligned with human values and the well-being of all living beings. This article contributes to the growing discourse on spirituality-based technology ethics and offers an alternative perspective for more humanistic science education.